Bibliometric and visual analysis in the field of ketogenic diet on cancer from 2012 to 2021 - Li, Rongrong; Huang, Qingcheng; Ye, Chenxiao; Wu, Changhong; Luo, Ning; Lu, Yi; Fang, Jianqiao; Wang, Yun (Frontiers in Nutrition, 2022)
Increasing evidence demonstrated that the ketogenic diet (KD) played a positive effect on cancer treatment. However, no systematic review and bibliometric analysis were conducted in this field. This study aimed to explore the current status, and reveal the potential trends and hotspots to provide a reference for future research. Publications were extracted from the Web of Science Core Collection. CiteSpace (5.6.R3) software and the website of bibliometrics were used for visual analysis. A total of 500 publications with 334 articles and 166 reviews were included, with the timespan of 2012 to 2021. The United States was the most productive country. Majority of the top 10 institutions were from the United States, and Harvard University was the top-contributing institution. The most prolific author and the co-cited author was Thomas N Seyfried from Boston College. The highest cited reference was published in Plos One, authored by Abdelwahab Mohammed G, with 161 citations. Glioma and breast cancer were the most common types of cancer in this field, while hepatocellular carcinoma and pancreatic cancer were the new hotspots. The anti-tumor mechanism of KD mainly focused on regulating metabolism, decanoic acid, oxidative stress, fatty acid oxidation, and cell apoptosis. Additionally, the presence of “chemotherapy” and “radiotherapy” in the keywords indicated that KD combined with anti-tumor research was a topic, while “immunotherapy” has became a recent frontiers. Notably, as a metabolic therapy, KD was deserved more attention in the treatment of hepatocellular carcinoma and pancreatic cancer, and KD combined with immunotherapy was the new hotspot and frontier. Additionally, more molecular studies and high-quality uniformly, randomized, controlled clinical trials are urgently warranted to evaluate the effect of KD in multiple cancers.